Clinical profile of ocular trauma in a tertiary care hospital of Southern Rajasthan - Mohanty, Lipa; Bhayani, Janki; Shah, Abhishek; Patel, Nishant; Patel, Aval (International Journal of Research in Medical Sciences, 2021)
Background: Ocular trauma is a major cause of preventable visual impairment and blindness leading to permanent loss of vision and deterioration of quality of life. 90% of the injuries are preventable. Aim of the current study was to study the clinical profile of patients with ocular trauma at a tertiary care hospital in Southern Rajasthan. Current study was a cross- sectional, observational study was conducted at Geetanjali medical college and hospital, Udaipur. Methods: After taking a well-informed consent a generalized detailed history of 108 cases (123 injured eyes) was obtained. Assessment of best corrected visual acuity, near vision, intraocular pressure, slit-lamp evaluation and dilated fundus examination was carried out. Then injury was classified as per BETTS classification. Patients with corneal foreign bodies and chemical injuries were recorded separately. Imaging modalities like ultrasound B-scan, CT-scan and MRI were employed wherever required. Results: Number of males (98) was much higher than females (9) in our study. Male: female ratio was found to be 10.8:1. The most commonly affected age group was 21-30 years, this highlights the alarmingly high incidence of ocular injuries in economically active young males. Farming is the primary occupation across India, hence it deserves a special mention. 22% of injury cases in our study were farm- work related injuries. Farmers need to be educated and provided eye protective equipment during high-risk activities. Laws regarding agricultural code of practice should be implemented and followed. Conclusions: In our study, not a single case out of 108 had used eye protection at the time of injury. Every effort should be made to create awareness regarding use of safety measures during driving and engaging in high-risk occupations. This will help prevent sight-threatening complications of ocular trauma and the deleterious impact on quality of life.